Biomarkers for dementia and other neurodegenerative diseases : Current developments - Wiltfang, J.; Lewczuk, Piotr; Otto, M. (Der Nervenarzt, 2016)
Cerebrospinal fluid-based neurochemical dementia diagnostics (CSF-NDD) support the early and differential diagnosis of dementia, most importantly the diagnosis of early or preclinical Alzheimer's dementia (AD). Meanwhile CSF-NDD are now recommended for improved exclusion and positive diagnostics of AD by the German national neuropsychiatry S3 dementia guidelines ( www.DGPPN.de ). Meta-analyses of independent international multicenter studies have shown that a combined CSF analysis of amyloid-beta 1-42 (A? 1-42, decreased), total tau proteins (increased) and phospho-tau proteins (increased) offers a sensitivity and specificity of 80-90 % for the early and differential diagnosis of AD (AD versus all other). Generally, CSF-NDD should be combined with blood-based routine diagnostics and should be part of routine CSF diagnostics, e. g. cell count and cell differentiation (if applicable), intrathecal antibody synthesis and blood-CSF barrier analysis. The CSF-NDD are most valuable for the improved differentiation between reversible dementia syndromes and irreversible neurodegenerative dementia, e. g. cognitive deficits due to late onset depression (pseudodementia due to depression) or AD. Combined with extended psychometric neuropsychological evaluation and neuroimaging methods, such as magnetic resonance imaging (MRI), dopamine transporter scanning (DaTscan) by single photon emission computed tomography (SPECT), 18F-fluorodeoxyglucose positron emission tomography (glucose-PET) and amyloid-PET, CSF-NDD also significantly improve the differential diagnostics within the heterogeneous group of primary neurodegenerative dementias. Meanwhile, several independent studies have indicated that the A? 1-42:A? 1-40 ratio is superior to the determination of A? 1-42 alone. Currently, several international research initiatives have been launched to further harmonize and optimize preanalytical procedures and CSF-NDD biomarker assays.
EVALuna2:23755